Comparative Study of Crack Width Prediction Models for Reinforced Concrete Beams - Vlora Shatri; Burbuqe Shatri; Armend Mujaj; Bajram Shefkiu (Salehan Institute of Higher Education, 2026)
Crack-width control is a critical serviceability limit state (SLS) requirement in reinforced concrete (RC) structures, as excessive cracking can compromise durability and accelerate reinforcement corrosion. This study evaluates the accuracy of crack width prediction models within major international design standards. An experimental investigation was conducted on a RC beam subjected to four-point bending, where crack propagation, beam deflections, and reinforcement stresses were monitored throughout the loading process. The measured crack widths were compared with analytical predictions from Eurocode 2 (EN 1992-1-1), DIN 1045-1, and ACI-based formulations. The results indicate that while all evaluated codes capture the general trend of increasing crack width with rising steel stresses under incremental loading, significant discrepancies exist in their predicted magnitudes. In general, it is Eurocode 2 that consistently provides the most conservative estimates, whereas DIN 1045-1 yields slightly lower but also consistent values of the same. Conversely, ACI-based approaches tend to underestimate crack widths at higher load levels. This study highlights the influence of modeling assumptions—specifically those related to bond-slip behavior, crack spacing, and tension stiffening—on the reliability of crack-width predictions. The results provide experimental evidence regarding the reliability and limitations of common predictive methods, contributing to a refined understanding of design rules for the serviceability of RC structures.